IMPLICATIONS OF CHILD PERFECTIONISM ON PSYCHOLOGICAL WELFARE: GUIDELINES FOR DIAGNOSIS AND CLINICAL PRACTICE - Oros, Laura Beatriz (Anales de Psicología / Annals of Psychology, 2005)
The purpose of this paper is to show that child perfectionism, which may seem harmless and even desirable, entails innumerable negative consequences regarding physical and emotional health in children. Various viewpoints are discussed which support the idea that perfectionism originates as a factor of psychological vulnerability, which should not only be diagnosed in time, but should also be treated appropriately with the objective of preventing future disorders. Thus, we propose some useful guidelines regarding clinical diagnosis and therapy.